An introduction to text mining research design, data collection, and analysis - Ignatow, Gabe; Mihalcea, Rada 1974- (Sage, 2018)
The book covers the most critical issues that must be taken into consideration for research projects, including web scraping and crawling, strategic data selection, data sampling, use of specific text analysis methods, and report writing. In addition to covering technical aspects of various approaches to contemporary text mining and analysis, the book covers ethical and philosophical dimensions of text-based research and social science research design.